Barbari ostili o pacifici interlocutori? Traci e Greci ad Apollonia Pontica (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
The Greek apoikia of Apollonia Pontica, which is nowadays located on Bulgarian shore of the Black Sea in a strategic area, represents an interesting case study for the Greek colonisation in the Póntos Eúxeinos. Its historical and geographical characteristics determined the importance of Apollonia Pontica in the context of the Greek presence  in the area, and the site rapidly became a crossroad both for Greek colonists and for the inhabitants. Recent archaeological data have shed new light on the  relationship between the two groups, providing essential elements for the interpretation of epigraphical, numismatic and literary sources. In this path, the present contribution aims at highlighting the cultural and commercial network in the area.
Keywords: Apollonia Pontica; colonisation; archaeology; Black Sea; cultural meeting